Effect of Terracing on Some Physieo-chemical Properties of Soil in the Uplands of Chotanagpur - Sinha, A.K.; Alam, S.M. (Journal of Soil and Water Conservation, 2022)
The uplands of Chotanagpur locally known as ’Tarn’ lands are being subjected continuously to various degrees and kinds of erosion resulting in depletion. Programme Evaluation Organisation, Planning Com- mission, Government of India, in its report (1964) while quoting a survey data for Chotanagpur brought the information that in about 45 years approximately 17% of the area surveyed had gone out of cultivation due to gully formation. This projects the problem quite clearly. To combat this menance Soil Conservation Wing of the Agricultural Department, Bihar have taken up the construction of terraces on eroded lands. Mainly two types of terraces are commonly constructed i.e. graded terrace, the suitability of which was confirmed by Mirchandani and Manrai (1959) and tad terrace which was designed by the Damodar Valley Corporation authorities to accommodate the liking of local people for rectangular plots and the aim of converting these lands into bench terraced land in due course of time (Prasad, 1961).